2012
DOI: 10.1371/journal.pone.0045727
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR-30b in the Developing Mouse Mammary Gland Causes a Lactation Defect and Delays Involution

Abstract: BackgroundMicroRNA (miRNA) are negative regulators of gene expression, capable of exerting pronounced influences upon the translation and stability of mRNA. They are potential regulators of normal mammary gland development and of the maintenance of mammary epithelial progenitor cells. This study was undertaken to determine the role of miR-30b on the establishment of a functional mouse mammary gland. miR-30b is a member of the miR-30 family, composed of 6 miRNA that are highly conserved in vertebrates. It has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 63 publications
5
49
0
1
Order By: Relevance
“…Despite the established role of a variety of extrinsic and intrinsic signals regulating mammary gland development (Howard and Gusterson 2000;Macias and Hinck 2012), a restricted number of studies have identified and validated miRNAs with a role in any aspect of normal mammary gland biology (Avril-Sassen et al 2009;Tanaka et al 2009;Ucar et al 2010;Yang et al 2010;Cui et al 2011;Le Guillou et al 2012), and even fewer have studied their function using transgenic animal models (Ucar et al 2010;Le Guillou et al 2012). Here we unveiled the miRNA cluster miR-424(322)/503 as an important regulator of the massive reorganization that occurs in the mammary epithelium after pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the established role of a variety of extrinsic and intrinsic signals regulating mammary gland development (Howard and Gusterson 2000;Macias and Hinck 2012), a restricted number of studies have identified and validated miRNAs with a role in any aspect of normal mammary gland biology (Avril-Sassen et al 2009;Tanaka et al 2009;Ucar et al 2010;Yang et al 2010;Cui et al 2011;Le Guillou et al 2012), and even fewer have studied their function using transgenic animal models (Ucar et al 2010;Le Guillou et al 2012). Here we unveiled the miRNA cluster miR-424(322)/503 as an important regulator of the massive reorganization that occurs in the mammary epithelium after pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs post-transcriptionally regulate gene expression mainly by targeting mRNAs for cleavage, translational repression, and mRNA destabilization. A very limited number of studies have identified and validated miRNAs with a role in any aspect of normal mammary gland biology (Avril-Sassen et al 2009;Tanaka et al 2009;Ucar et al 2010;Yang et al 2010;Cui et al 2011;Le Guillou et al 2012), and even fewer have studied their function in vivo (Ucar et al 2010;Le Guillou et al 2012). …”
mentioning
confidence: 99%
“…42,43 The functional activity of milkderived miRNAs is not universally accepted, and the other, nutritional hypothesis argues that miRNAs are not absorbed into the circulation, but they are degraded to nucleotides, which merely serve as nutrients. 42 The nutritional hypothesis is based on 3 mouse models 42 (i. transgenic mice overexpressing miR30b, 44 and ii. miR-375 and iii.…”
Section: Dietary Milk-derived Mirnasmentioning
confidence: 99%
“…42 In the first model, transgenic mice overexpressing miRNA-30b have been investigated. miR-30b is involved in the regulation in lactation, 44 and it inhibits phagocytosis in myeloid inflammatory cells, as well. 42,46 Significantly increased concentration of miR-30b was observed in the milk of transgenic mice, but no alteration in its concentration in milk-fed pup tissues was found.…”
Section: Dietary Milk-derived Mirnasmentioning
confidence: 99%
“…High expression of miR-103-1 at lactation 3 d might be involved in the initiation of lipid and fat secretion during early lactation. Furthermore, miR-126-3P, miR-129-5P, miR-484-5p, miR-93a, and miR-30b are important in the inhibition of mammary cell proliferation or differentiation (Cui et al, 2011;Li et al, 2012a;Le Guillou et al, 2012). For example, miR-126-3p inhibited protein expression of progesterone receptor (PGR) and the proliferation of mammary epithelial cells, and therefore played an important role in the process of mammary gland development (Cui et al, 2011).The miRNA-30b family might play a role in the differentiation of adipocytes (Lin et al, 2010;Zaragosi et al, 2011), B-cells (Lin et al, 2010), and osteoblasts (Wu et al, 2012).…”
Section: Mirnas Related To Mammary Development Had Asimilar Expressiomentioning
confidence: 99%